Effects of periodontopathic bacterial extracts on human periodontal fibroblasts - San Miguel, S. (The Journal of the Philippine Dental Association)
Bacterial effects on in vitro mineralization of human periodontal fibroblasts (HPF) have not yet been examined in great detail. In our study, we developed a model to determine the effects of soluble extracts of the periodonto- pathic bacteria Porphyromonas gingivalis (P.g.), Bacteroides forsythus (B.f.) and Trepo- nema denticola (T.d.) on cell proliferation as well known osteoblastic markers present in HPF cultured in vitro (alkaline phosphatase (ALP) activity, collagen content. Periodontal fibroblasts stimulated by B-glycerophosphate, ascorbic acid, and dexamethasone (BAD) were compared to unstimulated cells. The extracts obtained from the periodontal pathogens had a suppressing effect on the growth of HPF and decreased ALP activity within 24 hours after application. While extracts obtained from P.g. and B.f. induced a slight reduction of collagen content in BAD-stimulated HPF cells, T.d. extracts led to an increase of collagen. Our data suggest that periodontopathic bacteria may suppress tissue regeneration in vivo not only by activating host defense mechanisms but also directly via a suppression of growth and differentiation of HPF.